COMPARATIVE ANALYSIS OF TRADITIONAL AND DIGITAL ASSESSMENT SYSTEMS - Azimqulov Sayxun (Modern American Journals, 2025)
This study examines the key differences between traditional and digital assessment systems in higher education, with a particular focus on pedagogical universities specializing in information and communication technologies. The research analyzes how each assessment approach measures learning outcomes, supports feedback, and influences the effectiveness of the educational process. Traditional assessment systems are characterized by structured formats and established evaluation criteria, while digital assessment systems offer greater flexibility, efficiency, and opportunities for immediate feedback. The study highlights the pedagogical advantages and limitations of both systems and emphasizes the importance of selecting assessment methods that align with instructional objectives and learner needs.
Keywords: Traditional assessment, digital assessment, educational evaluation, learning outcomes, ICT in education, higher education, pedagogical measurement.